2001
DOI: 10.1128/jcm.39.12.4583-4584.2001
|View full text |Cite
|
Sign up to set email alerts
|

Case of Catheter Sepsis with Ralstonia gilardii in a Child with Acute Lymphoblastic Leukemia

Abstract: Acute lymphoblastic leukemia was diagnosed in a 7-year-old girl. Two months after insertion of a central venous catheter, she developed fever and complained of headache and abdominal pain. Physical examination revealed no focus of infection. A gram-negative nonfermenting bacillus was recurrently cultured from blood. Extensive biochemical testing and 16S ribosomal DNA sequencing led to the identification of Ralstonia gilardii. CASE REPORTAcute lymphoblastic leukemia (ALL) was diagnosed in a 7-year-old girl in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 6 publications
5
31
1
2
Order By: Relevance
“…To our knowledge, the presented case represents the first fatal infection caused by this organism. Intriguingly, our case of C. gilardii infection is quite similar to the case presented by Wauters et al (9). In both situations, the patients were young and immunocompromised.…”
Section: Case Reportsupporting
confidence: 72%
See 3 more Smart Citations
“…To our knowledge, the presented case represents the first fatal infection caused by this organism. Intriguingly, our case of C. gilardii infection is quite similar to the case presented by Wauters et al (9). In both situations, the patients were young and immunocompromised.…”
Section: Case Reportsupporting
confidence: 72%
“…Furthermore, C. gilardii has been identified in respiratory secretions of cystic fibrosis patients (2,3). The only reported clinical infection caused by C. gilardii was described by Wauters et al in 2001. In this case, the organism was the cause of catheter-related sepsis in a 7-year-old female patient with acute lymphoblastic leukemia (9).…”
Section: Case Reportmentioning
confidence: 86%
See 2 more Smart Citations
“…Strains of R. mannitolilytica (formerly known as 'Pseudomonas thomasii' and R. pickettii biovar 3) have also been isolated from various clinical sources, including nosocomial recurrent meningitis (Philips et al, 1972;De Baere et al, 2001;Vaneechoutte et al, 2001). R. gilardii, R. paucula and R. taiwanensis have been isolated both from human clinical samples and from the environment Vandamme et al, 1999;Chen et al, 2001;Wauters et al, 2001). Recent studies have demonstrated that R. pickettii, R. mannitolilytica, R. gilardii and R. taiwanensis can also be recovered from the respiratory tract of cystic fibrosis (CF) patients (Chen et al, 2001;Coenye et al, 2002a, b).…”
Section: Introductionmentioning
confidence: 99%